Strategic decision making method for sharing resources among multiple manufacturing/remanufacturing systems - Shinsuke Kondoh; Timo Salmi (Journal of Remanufacturing, 2011)
Purpose: To reduce products' environmental impact over their entire life cycle, adequate reuse and recycling of products and their components are indispensable. In this context, it is important to establish efficient closed-loop manufacturing systems (CMS), where products are made from post-use as well as new materials. However, the establishment of economically and environmentally efficient CMS is difficult due to the uncertainty associated with the return flows of post-use products. Since product usage conditions and lifetimes differ from user to user, there are significant fluctuations in product flows' quantity and quality. This results in insufficient utilization of manufacturing/remanufacturing resources (e.g., labor and equipment) and high investment costs for CMSs, which hinder proper reuse and recycling of post-use products. The objective of this study is to propose a strategic decision-making method for sharing resources among multiple CMSs to reduce the cost of product reuse and recycling. Methods: We first discuss the benefits and difficulties of sharing production resources among multiple CMSs. Then, a transferability benefit index (TBI) is introduced to help identify the most promising resources to be shared among multiple systems. Results :A simplified example calculation is provided as an illustration of the method. Two disassembly systems with the similar structure are considered as a case study. As a result, we successfully applied the index to determine the most promising resources in a case study. Conclusions: We find that TBI is useful because it provides a simple and easily understandable decision criterion for identifying the resources to be transferred and shared among multiple CMSs to reduce the cost for reuse and recycling of used products. TBI also screens outs the promising resources which should be redesigned and modified before sharing among multiple CMSs. Development of practical redesign methods and modification guidelines for these resources will be included in our future work of this study.
Keywords: 650; closed-loop manufacturing system (CMS); cost for reuse and recycling; sharing resource; transferability benefit index (TBI); design structure matrix (DSM); Produktionswirtschaft; Betriebliche Kreislaufwirtschaft; Produktionskosten; Strategisches Management